Inhibition of Platelet Aggregation by Dialysable Fibrinogen Degradation Products (FDP) - Stachurska, Jolanta; Latałło, Z; Kopeć, Maria (Thrombosis and Haemostasis, 1970)
During prolonged proteolysis of fibrinogen by plasmin dialysable, low molecular fragments accumulate which inhibit platelet aggregation induced by thrombin, ADP, adrenaline and noradrenaline. These fragments isolated by dialysis were separated on sephadex G-25 column. The active component has probably a molecular weight lower than 5,000 and does not contain aromatic amino acids.